Gambaran Pengetahuan Mitigasi Gunung Api pada Anak-Anak Panti Asuhan Darul Alfalah Denpasar Provinsi Bali - Maharani, Nia; Krisna, Evi Dwi (UNIB Press, 2025)
This study is a continuation of the community services activities of the author and the Community Service (PKM) team in 2022 at same location mamely the Darul Alfalah Orphanage Pemogan Village Denpasar District, South Denpasar District. The activty included socialization of earthquake and their mitigation qmd finding out how much knowledge the orphanage children had about earthquakes and their mitigation (Maharani, 2022). This study focus on volcanic mitigation in orphanages with orphanage children as respondents. The questionnaire contained queastions about the efforts taken before during and after the volcanic eruption. The results of questionnaire showed the orphaange children still lacked knowledge in efforts to minimize the dangers of volcanic eruptions.